User guide to the multi-stakeholder framework for intervening in root, tuber and banana seed systems. RTB User Guide - Bentley, J.W.; Mudege, Netsayi N.; Andrade-Piedra, J.L. (International Potato Center, 2020)
This user’s guide presents a tool, called the ‘multi-stakeholder framework for intervening in root, tuber and banana seed systems.’ It is designed to help any interested person to understand seed systems of these crops or to improve interventions (e.g., projects or programs) in them. The framework may be graphed as a table, with rows of stakeholders (e.g., policymakers, researchers, and seed producers) and columns of characteristics: availability of seed, access, and quality. Access includes delivery channels, affordability, and awareness. Seed quality includes crop variety and other issues (health, genetic purity, physiological age, and physical quality). Gender should always be taken into account when using the framework.